(untitled) (Global Journal of Management and Business Research, 2018)
Human Resource Planning (HRP) is considered as the first and primary practice of human resource management and plays a crucial role in determining the success of organization. Effective human resource planning allows management to recruit, develop and deploy the right people at the right place at the right time, to meet organizational internal and external service level commitments. Most public organization in Sri Lanka today are facing challenges regarding implementing the effective HRP in order to achieve their goals and objectives. In this sense, indigenous hospitals also face challenges to implement proper HRP system to provide quality service and achieve patient’s satisfaction. In Sri Lankan context, the topic effective HRP in Ayurvedic Hospitals rarely conducted in the past. Hence, there is a research gap prevailing there. Therefore, in order to fill this research gap, this study was conducted with the objective of explore the HRP in OPD at Ayurvedic hospitals in Vavuniya district. In order to achieve the study objectives, primary data were collected from 67 staff of Ayurvedic Hospitals in Vavuniya district. The data were analyzed by using univariate analysis. Findings of the study revealed that, Ayurvedic Hospitals in Vavuniya district implementing HRP in a low level. Moreover, this study provides some recommendations to further improve the HRP system of Ayurvedic hospitals. This study is useful to improve the quality of HRP system in the organization.